2016
DOI: 10.2147/cia.s113287
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of L-carnitine supplementation on frailty status and its biomarkers, nutritional status, and physical and cognitive function among prefrail older adults: a double-blind, randomized, placebo-controlled clinical trial

Abstract: BackgroundFrailty is a biological syndrome of decreased reserve and resistance to stressors due to decline in multiple physiological systems. Amino acid deficiency, including L-carnitine, has been proposed to be associated with its pathophysiology. Nevertheless, the efficacy of L-carnitine supplementation on frailty status has not been documented. Thus, this study aimed to determine the effect of 10-week L-carnitine supplement (1.5 g/day) on frailty status and its biomarkers and also physical function, cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 51 publications
2
50
0
Order By: Relevance
“…This result was consistent with the previous literature (Danon-Hersch et al, 2012). However, many studies revealed that being female was also a contributing factor to frailty syndrome (Alvarado et al, 2008;Ávila-Funes et al, 2011;Collard et al, 2012, Mitsionis et al, 2009, Badrasawi et al, 2016.…”
Section: Ijphcssupporting
confidence: 93%
“…This result was consistent with the previous literature (Danon-Hersch et al, 2012). However, many studies revealed that being female was also a contributing factor to frailty syndrome (Alvarado et al, 2008;Ávila-Funes et al, 2011;Collard et al, 2012, Mitsionis et al, 2009, Badrasawi et al, 2016.…”
Section: Ijphcssupporting
confidence: 93%
“…Exercise may also have positive effects in frailer populations, but the most effective components of this are unclear. 171 Two further RCTs that have been published since our systematic review searches, of l-carnitnine supplementation 172 and an exercise and nutrition intervention, 173 found similarly mixed effects on frailty symptoms and physical functioning.…”
Section: Evidence Reviews: Discussionmentioning
confidence: 90%
“…Furthermore, L‐carnitine decreased adipocyte size and did not negatively impact inflammatory markers. L‐carnitine supplementation has previously been shown to improve markers of mitochondrial and metabolic function in aged rodents (Hagen et al ., ; Noland et al ., ) and has also been shown to improve some biochemical and functional parameters in the elderly (Malaguarnera et al ., ; Badrasawi et al ., ). In the heart, L‐carnitine appeared to have stronger activity than pioglitazone, as it altered the expression of three transcriptional markers of CR in a manner consistent with CR mimicry.…”
Section: Discussionmentioning
confidence: 97%